2015
DOI: 10.1007/978-3-319-22822-8_5
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin Structure of Epstein–Barr Virus Latent Episomes

Abstract: EBV latent infection is characterized by a highly restricted pattern of viral gene expression. EBV can establish latent infections in multiple different tissue types with remarkable variation and plasticity in viral transcription and replication. During latency, the viral genome persists as a multi-copy episome, a non-integrated-closed circular DNA with nucleosome structure similar to cellular chromosomes. Chromatin assembly and histone modifications contribute to the regulation of viral gene expression, DNA r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 212 publications
0
28
0
Order By: Relevance
“…Chromatin structure and epigenetic modifications contribute significantly to the regulation of EBV latency 5,7 . In the majority of EBV latent infections, the viral genome persists in the nucleus as a chromatinized, covalently closed, circular genome that closely tracks with the host chromosome during cell division cycle.…”
mentioning
confidence: 99%
“…Chromatin structure and epigenetic modifications contribute significantly to the regulation of EBV latency 5,7 . In the majority of EBV latent infections, the viral genome persists in the nucleus as a chromatinized, covalently closed, circular genome that closely tracks with the host chromosome during cell division cycle.…”
mentioning
confidence: 99%
“…Previous studies have indicated that episome maintenance is mechanistically linked to the establishment of chromatin structures and epigenetic modifications that stabilize viral chromosome transmission during mitosis and viral gene expression during latency [43]. Failure to establish stable epigenetic repression leads to the aberrant expression of lytic cycle genes and lytic DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…While we note that latency III transcripts are induced in Burkitt cell EBV lytic reactivation (27), we speculate that CAF1 depletion may perturb maintenance of EBV genomic DNA methylation through effects on crosstalk between histone and DNA methylation pathways. ChIP-seq approaches demonstrated H3K9me3 and H3K27me3 repressive marks at key lytic and latency gene sites (61, 80, 81). Furthermore, we recently found domains of the enzyme UHRF1 that read H3K9me2/me3, the H3 N-terminus and hemi-methylated DNA are essential for EBV latency I (73).…”
Section: Discussionmentioning
confidence: 99%